The Contrasting Effects of Education on Fertility over Time Casalguidi, 1819–1960. Issue 3 (26th July 2021) - Manfredini, Matteo; Breschi, Marco; Fornasin, Alessio
Abstract: Education has been frequently claimed to shape demographic outcomes. Mortality, fertility, and nuptiality have all been attested to be affected to some extent by education attainment. This article investigates the effects of education on fertility over time in a rural Italian community once controlled for potential confounders. Using individual-level data drawn from various sources, the study analyzes the role of education in shaping reproductive behaviors not only during the demographic transition (1890–1960) but also in the pretransitional period (1819–59). The results highlight the contrasting effects of literacy on fertility, which passed from a positive association in the ancien régime to a negative one in the transitional phase. Educated couples were therefore forerunners in the process of fertility decline because they were not only in the position to be the most pressed to control reproduction but also because they were likely aware of reproductive mechanisms, had the knowledge of more effective birth-control methods, had the economic possibility to get them, and had the necessary capacity to use them.